The Relationship Between Self-Care Management and Blood Pressure Status of Hypertension Patients - Rara Puspita Anjarwati; Fahrun Nur Rosid (Jurnal Ners, 2026)
Background : Hypertension is a condition where systolic blood pressure increases to more than 140 mmHg and diastolic blood pressure increases to more than 90 mmHg. Hypertension is currently a problem in developing and developed countries. If not treated properly, high blood pressure can trigger complications of various diseases. Patients with high blood pressure and hypertension can do self-care management to optimize factors that specifically affect hypertension and increase the risk of complications. Objective : In this study, the researcher aims to analyze the relationship between self-care behavior and blood pressure status in hypertensive patients at the Health Center. Method : In this study, the researcher used a quantitative research type with a cross-sectional design. The data collection method used the Self-Care Management Behavior Questionnaire (HSMBQ) questionnaire and blood pressure measurement using a Sphynomanometer. Benefits : This study can be useful for hypertension patients and the health professional team that serves them. This study is also expected to be a foundation for previous researchers Keywords: Self Care, Blood Pressure, Hypertension.